O nieobecności figury matki i jej ekwiwalentach w twórczości poetyckiej Małgorzaty Lebdy - Borto, Kinga (Zagadnienia Rodzajów Literackich, 2025)
The subject of the article is the matter of the absence of the maternal figure in Małgorzata Lebda’s poetry and its influence on the construction of the lyrical persona. In my analyses, I focus on the representation of the figure of the mother as an absence that is complemented by other relations — primarily with the father and sisters. In order to investigate the phenomena, I am interested in I use Ryszard Nycz’s concept of the sylleptic subject, which makes it possible to interpret the poet’s work from the perspective of her biography, as well as to grasp the tension between autobiography and fiction and to partially unite the figure of the author and the lyrical persona. The analysis of the three poetry books — Granica lasu, Matecznik and Sny uckermärkerów — will allow me to show the evolution of the female subject and the working through of the trauma after the loss of her parents. In order to consider elements of the author’s biography, I will also take into consideration several interviews in which the poet shares details from her private life that have influenced her poetic work.